PDE3A-SLCO1C1 locus is associated with response to anti-tumor necrosis factor therapy in psoriatic arthritis. (November 2014) - Julià, Antonio; Rodríguez, Jesús; Fernández-Sueiro, José Luis; Gratacós, Jordi; Queiró, Rubén; Montilla, Carlos; Torre-Alonso, Juan Carlos; Pérez-Venegas, José Javier; Manrique-Arija, Sara; Muñoz-Fernández, Santiago; González, Carlos; Roig, Daniel; et al.
Aim: Variation at PDE3A-SLCO1C1 locus has been recently associated with the response to anti-TNF therapy in rheumatoid arthritis. We undertook the present study to determine whether PDE3A-SLCO1C1 is also associated with the response to anti-TNF therapy in psoriatic arthritis.Patients & methods: Genomic DNA was obtained from 81 psoriatic arthritis patients that had been treated with anti-TNF therapy. PDE3A-SLCO1C1 SNP rs3794271 was genotyped using Taqman realt-time PCR. The clinical response to anti-TNF therapy was measured as the change from baseline in the level of disease activity according to the DAS28 score.Results: A significant association between rs3794271 and anti-TNF response in psoriatic arthritis was found (beta = -0.71; p = 0.0036).Conclusion: PDE3A-SLCO1C1 locus is also associated with response to anti-TNF therapy in psoriatic arthritis. Original submitted 12 May 2014; Revision submitted 18 August 2014